The Sudden Dominance of blaCTX–M Harbouring Plasmids in Shigella spp. Circulating in Southern Vietnam - Nguyen, N; Ha, V; Tran, N; Stabler, R; Pham, D; Le, T; Van Doorn, H; Cerdeño-Tárraga, A; Thomson, N; Campbell, J; Nguyen, V; Tran, T; et al. (Public Library of Science, 2010)
BACKGROUND: Plasmid mediated antimicrobial resistance in the Enterobacteriaceae is a global problem. The rise of CTX-M class extended spectrum beta lactamases (ESBLs) has been well documented in industrialized countries. Vietnam is representative of a typical transitional middle income country where the spectrum of infectious diseases combined with the spread of drug resistance is shifting and bringing new healthcare challenges. METHODOLOGY: We collected hospital admission data from the pediatric population attending the hospital for tropical diseases in Ho Chi Minh City with Shigella infections. Organisms were cultured from all enrolled patients and subjected to antimicrobial susceptibility testing. Those that were ESBL positive were subjected to further investigation. These investigations included PCR amplification for common ESBL genes, plasmid investigation, conjugation, microarray hybridization and DNA sequencing of a bla(CTX-M) encoding plasmid. PRINCIPAL FINDINGS: We show that two different bla(CTX-M) genes are circulating in this bacterial population in this location. Sequence of one of the ESBL plasmids shows that rather than the gene being integrated into a preexisting MDR plasmid, the bla(CTX-M) gene is located on relatively simple conjugative plasmid. The sequenced plasmid (pEG356) carried the bla(CTX-M-24) gene on an ISEcp1 element and demonstrated considerable sequence homology with other IncFI plasmids. SIGNIFICANCE: The rapid dissemination, spread of antimicrobial resistance and changing population of Shigella spp. concurrent with economic growth are pertinent to many other countries undergoing similar development. Third generation cephalosporins are commonly used empiric antibiotics in Ho Chi Minh City. We recommend that these agents should not be considered for therapy of dysentery in this setting.